PENYULUHAN DAN PEMBERIAN TABLET FE PADA REMAJA PUTRI UNTUK MENCEGAH ANEMIA DI MA AZZIKRA TANA TORAJA - Usman, Usman; Nur Hana, Nur Hana; Erlin, Erlin; Sarmila, Sri Ayu; Novianti, Eva; Hamiati, Hamiati; Fadillah, Alya Dwi; Ernawati, Ernawati (Media Literasi Indonesia, 2025)
Iron deficiency anemia is a common health problem among adolescent girls due to increased iron requirements during growth and menstruation. Lack of knowledge about anemia prevention and low adherence to iron tablet consumption are the main factors contributing to the high prevalence of anemia. This community service activity aims to improve adolescent girls' understanding of anemia and encourage compliance with iron supplementation through health education and iron supplementation. The method used in this activity includes interactive lecture-based health education and discussions, as well as the provision of iron tablets. Evaluation was conducted by comparing participants' knowledge levels before and after counseling. The results showed a significant increase in participants' understanding of anemia after the intervention. This program contributes to the development of knowledge in health education by providing effective strategies for anemia prevention in adolescent girls. It is hoped that this activity can serve as a model for sustainable school health programs.